POSTURAL BALANCE, MUSCLE STRENGTH, AND FALL RISK IN ELDERLY WITH CHRONIC OSTEOMYARTICULAR DISEASE OSTEOMUSCULOSKELETAL - Ribeiro dos Santos, Maria Eduarda; Enes Ferreira, Camilly; Costa, Jamilly Morattely Fontes; Oliveira, Cláudia Santos; Parreira, Rodolfo Borges; Oliveira, Deise Aparecida de Almeida Pires (CIPEEX, 2025)
Longevity brings new challenges that demonstrate the importance of healthy aging and the inclusion of the elderly in society. However, many elderly people find it difficult to maintain their ability to move autonomously and safely, thus, the restriction of mobility can cause various undesirable consequences, such as an increased risk of falls and loss of independence. Thus, the objective of the study is to verify the relationship between lower limb muscle strength, postural balance, and the risk of falls in elderly individuals with osteomyoarticular diseases. This is a cross-sectional analytical observational study. The study population consisted of 106 elderly individuals regularly enrolled at UniAPI, of which only 60 met the inclusion criteria. Sociodemographic information was collected and assessments were conducted on the incidence of falls, muscle strength, and static balance. In addition, the sit-to-stand test was used to assess lower limb muscle strength, and the Sway protocol on the force platform was used to verify static balance. The study demonstrated that those without knee osteomyoarticular disease perform more repetitions in the sit-to-stand test than those with osteomyoarticular disease, concluding that the risk of falls in the elderly with osteomyoarticular diseases is a concerning factor, and should be addressed through preventive measures aimed at improving bodily instability.